Antifouling activity of microorganisms associated with the marine organisms - Anjana Suresh; Grasian Immanuel (Novel Research in Microbiology Journal)
Biofouling is an ongoing problem in the marine industries that requires significant financial resources for control and new cleaning procedures. There is a feasible and immediate need to produce ecologically compatible low-toxic and harmless antifouling compounds for the maritime companies and underwater equipment; since the usage of Tributyltin (TBT) based marine coatings was banned globally in 2008. In recent years; the marine natural products have emerged as one of the most potential forms of antifouling agents. Although the natural antifoulants made from marine species; especially sponges and corals, have gained importance because of their performance in field tests; however, the gathering of larger quantities of marine animals is not a feasible choice. Several recent researches revealed that the marine microorganisms associated with sponges; corals, ascidians, seaweeds, and sea grasses, serve as the primary sources of antifouling substances and exhibit antimicrobial; antibacterial, and antifouling activity. During the screening of antifouling compounds; these marine microorganisms displayed antifouling ability against the macro and micro-foulers. This review aimed to focus on the improvements in the antifouling abilities of the natural products derived from marine organism-associated microorganisms.